PENGARUH VARIASI POSISI K-BRACED CBF TERHADAP PERILAKU STRUKTUR RANGKA BAJA 6 LANTAI DI KOTA PONTIANAK - Yufiansyah; Wida Ningsih; Iona Violeta (Jurnal Teknologi Infrastruktur, 2025)
ABSTRACT This study investigates the effect of K-braced Concentrically Braced Frame (CBF) variations on the structural behavior of a six-story steel frame building located in Pontianak with soft soil conditions (site class SE). The analysis was conducted using the equivalent lateral force method in accordance with SNI 1726:2019, with ten structural models simulated in ETABS. The parameters evaluated include natural period, maximum displacement, and inter-story drift. The results indicate that the structure without bracing exhibits the longest natural period and the largest lateral displacement. Full bracing installations on several bays (variations A1, A2, B1, B2, C1, and C2) significantly reduce the natural period and produce the smallest displacement and drift. In contrast, alternating bracing patterns (variations B3, D1, and D2) tend to increase structural flexibility, leading to reduced performance. Therefore, the configuration and distribution of bracing play a crucial role in enhancing the seismic performance of multi-story steel structures. Keywords: K-braced, Concentrically Braced Frame (CBF), Structure Period, Displacement, Drift